Composite coating electroplating process method

By adding nano-silica and titanium oxide and multi-complexing agent to the zinc-nickel alloy plating layer, the uniformity and dispersion ability of the plating solution are improved, and the problem of insufficient density and corrosion resistance of the traditional plating layer is solved, and high hardness is achieved and high corrosion resistance composite coating, suitable for complex parts such as high-speed train connections.

CN119265652APending Publication Date: 2025-01-07SHANDONG JIANZHU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411623123.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Traditional zinc-nickel alloy plating is difficult to meet the requirements of high hardness, corrosion resistance and uniform plating in high-speed train automotive connector applications, and the plating layer is poor in density, making it difficult to adapt to the uniformity and dispersion of plating liquid of complex shape parts.

Method used

The composite plating electroplating process is adopted, and the plating solution ratio includes sodium hydroxide, ZnO, nickel sulfate, triethanolamine, tetraethylene pentamine, EDTA, nanosilica and nanotitanium oxide, which is improved by alkaline plating solution and multivariate complexing agent. The uniformity and dispersion ability of the plating solution are used to refine the microstructure of the plating layer by using the nano-size effect to enhance its protective performance.

Benefits of technology

The corrosion resistance, hardness and density of zinc-nickel alloy coating have been significantly improved, and the porosity of the coating has been greatly reduced, and the corrosion resistance has been increased by more than 5 times. It is suitable for the high-performance needs of complex parts such as high-speed train connections.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265652A_ABST
    Figure CN119265652A_ABST
Patent Text Reader

Abstract

According to the composite plating layer electroplating process method, a plating solution comprises, by molar mass, 50%-80% of sodium hydroxide, 2%-3% of ZnO, 3%-7% of nickel sulfate, 2%-9% of triethanolamine, 0.4%-3% of tetraethylenepentamine, 1%-4% of sodium potassium tartrate tetrahydrate, 0.1%-1% of EDTA, 2%-7% of nano silicon dioxide, 0.6%-3% of nano titanium oxide, 12 mL / L of a primary brightener and 12 mL / L of a secondary brightener. By adding the nano silicon oxide and the titanium oxide, a multifunctional composite coating with enhanced surface hardness, self-lubrication, wear resistance and corrosion resistance can be produced, due to the nano size effect, the microstructure of the coating is refined, a finer grain structure is obtained, the compactness of the composite coating is improved, and the corrosion resistance is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of metal surface treatment, in particular to a composite coating electroplating process method. Background Art

[0002] Electroplated zinc-nickel alloy coatings have an important position in engineering applications for protecting metal materials from corrosion due to their excellent corrosion resistance. Although the performance of zinc-nickel alloy coatings has met the basic requirements of various applications, with the advancement of technology and the improvement of performance requirements, the existing electroplating technology still needs to be optimized, including poor coating density, low coating hardness, poor corrosion resistance, poor plating solution uniformity, etc. The present invention is mainly used in high-speed train automobile connectors. High-speed train connectors require the coating to have higher performance, including high hardness and high corrosion resistance. Due to the complex shape of the parts, in order to maintain the quality of the coating, the plating solution is required to have better uniformity and dispersibility. However, traditional zinc-nickel alloy coatings are difficult to meet such high performance requirements. Therefore, nanotechnology has opened up a new way to improve the performance of the coating, especially through the nano-size effect to refine the microstructure of the coating and enhance its protective performance. The unsaturation of nanoparticles can bond with nickel ions, etc., and pull ions to move in the plating solution, thereby improving the uniformity and dispersibility of the plating solution during the electroplating process. Summary of the invention

[0003] In order to solve the above problems, the present invention provides a technical solution, a composite coating electroplating process method, characterized in that the plating solution comprises, by molar mass ratio, 50%-80% sodium hydroxide, 2%-3% ZnO, 3%-7% nickel sulfate, 2%-9% triethanolamine, 0.4%-3% tetraethylenepentamine, 1%-4% potassium sodium tartrate, 0.1%-1% EDTA, 2%-7% nano silicon dioxide, 0.6%-3% nano titanium oxide, 12mL / L primary brightener, and 12mL / L secondary brightener; the process is as follows: temperature 15-30°C, plating solution pH: 12, cathode current density 4-6A / dm², cathode area: anode area is 1:1.2, and electroplating time: 15 minutes; the electroplating process flow comprises: a. Pour the calculated amount of sodium hydroxide into a small amount of water and stir to fully dissolve it; b. Pour the calculated amount of zinc oxide into the sodium hydroxide solution obtained in step a and stir to fully dissolve it; c. Pour the calculated amount of nickel sulfate into a small amount of water and stir to fully dissolve it; d. Pour the calculated amount of triethanolamine into the nickel sulfate solution obtained in step c and stir to fully dissolve it; e. Pour the calculated amount of tetraethylene pentamine, EDTA, and tartaric acid into a small amount of water, stir to fully dissolve, and pour into the solution obtained in d to fully dissolve; f. Mix the solution of step b and step e, stirring and dissolving until clear; J. Add the calculated amount of nano silicon oxide and nano titanium oxide to f, and stir evenly to make the nanoparticles suspended in the plating solution; h. Add the calculated amount of water to make up to volume.

[0004] Among them, sodium hydroxide 77.7%, ZnO 2.8%, nickel sulfate 5.5%, triethanolamine 4.5%, tetraethylenepentamine 1.4%, potassium sodium tartrate 2.1%, EDTA 0.2%, nano silicon dioxide 3.8%, nano titanium oxide 1.6% can achieve the best effect. In the paper Investigation on the coating modification effect of nano-SiO2particles on nano-TiO2 particles (DOI: 10.1088 / 2053-1591 / ab192d), the article mainly studies the use of sol-gel method to coat a layer of nano-silicon dioxide particles on the surface of nano-titanium dioxide particles, mainly to overcome the photocatalytic decomposition of the organic matrix of titanium dioxide. The difference between the present invention and the article is that nano-silicon dioxide and nano-titanium dioxide are applied in the field of electrodeposition, and the optimal ratio of silicon dioxide and titanium dioxide is found on the basis of the zinc-nickel alloy system, so that the zinc-nickel alloy coating achieves the best performance. The paper CeO2 modified SiO2 acted as additive in electrodeposition of Zn-Ni alloy coating with enhanced corrosion resistance (DOI: 10.1016 / j.jallcom.2017.11.031) prepared cerium oxide modified silicon dioxide as an additive for zinc-nickel coating electrodeposition. According to the analysis of the article, the electrodeposition used in the article is an acidic system. Nano-cerium dioxide is acidic and more suitable for participating in the modification of electrodeposition in the acidic plating solution system. The alkaline plating solution used in this article is less corrosive to equipment and workpieces. The alkaline plating solution can make the metal ions more evenly distributed and deposited, thereby obtaining a more uniform thickness coating. For parts with complex structures such as deep holes, grooves, and blind holes, alkaline plating solutions can better protect the quality of these parts. Nano-titanium dioxide and silicon dioxide are also alkaline, which are more suitable for participating in the improvement of electrodeposition in an alkaline system. At the same time, nano-silicon dioxide and titanium dioxide can absorb Zn in the plating solution. + 、Ni + It not only improves the stability of the plating solution, but also improves the throwing power of the plating solution.

[0005] Compared with the prior art, the present invention has the following advantages: the present invention is suitable for parts with high requirements for wear resistance and corrosion resistance. Compared with the traditional zinc-nickel alloy plating solution electroplating process, nano silicon oxide and nano titanium oxide are added to the plating solution. The precursors of nano silicon oxide and titanium oxide are ethyl orthosilicate and butyl titanate, respectively. They can be obtained more conveniently and at a lower cost by using the sol-gel method. In addition, nano silicon oxide is alkaline and easily absorbs OH. - , adsorption of OH - The back charge is negative, so it can react with Zn in the plating solution. + 、Ni + When nano silicon oxide and nano-oxidation states move, they can carry cations with them, which not only improves the stability of the plating solution, but also improves the throwing power of the plating solution. In addition, the addition of nano silicon oxide and titanium oxide can produce a multifunctional composite coating with enhanced surface hardness, self-lubrication, wear resistance and corrosion resistance. Due to the nano-size effect, the microstructure of the coating is refined, and a finer grain structure is obtained. The density of the composite coating is improved, and the corrosion resistance is greatly improved. The plating solution uses a multi-component complexing agent (triethanolamine, tetraethylenepentamine, EDTA, potassium sodium tartrate). According to experimental experience, the presence of nanoparticles makes it easy for the plating solution to produce bubbles, which can easily cause pinholes in the coating. However, the use of a multi-component complexing agent effectively reduces the wetting angle between the plating solution and the coating, and reduces the pinhole pits produced by the coating, so the porosity of the coating is greatly reduced. The corrosion resistance of the zinc-nickel alloy coating is more than 5 times higher than that of the zinc alloy coating of the same thickness. According to the literature, the nickel content in the coating is close to 14%, and the performance of the zinc-nickel alloy is optimal. Tetraethylenepentamine is unsaturated and can combine with nickel ions in the plating solution. During discharge, it is deposited on the cathode substrate, thereby increasing the nickel content of the coating, thereby improving the performance of the zinc-nickel alloy coating. The composite electroplating process takes into account the advantages of the nanosystem and the multi-component complexing agent, which greatly improves the corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0006] Figure 1 This is a scanning electron microscope image of the sample obtained in Example 1 at 5,000 times magnification; Figure 2 This is a scanning electron microscope morphology image of the sample obtained in Comparative Example 1 at 5,000 times magnification; Figure 3 This is a scanning electron microscope morphology image of the sample obtained in Comparative Example 2 at 5,000 times magnification. DETAILED DESCRIPTION

[0007] The present invention provides the following technical solutions: The following describes the implementation of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific implementations, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0008] The invention provides a technical solution: a composite coating electroplating process method, characterized in that the plating solution comprises, by molar mass ratio, 50%-80% sodium hydroxide, 2%-3% ZnO, 3%-7% nickel sulfate, 2%-9% triethanolamine, 0.4%-3% tetraethylenepentamine, 1%-4% potassium sodium tartrate, 0.1%-1% EDTA, 2%-7% nano silicon dioxide, 0.6%-3% nano titanium oxide, 12mL / L primary brightener, and 12mL / L secondary brightener; the process is as follows: temperature 15-30°C, plating solution pH: 12, cathode current density 4-6A / dm², cathode area: anode area is 1:1.2, and electroplating time: 15 minutes; the electroplating process flow comprises: a. Pour the calculated amount of sodium hydroxide into a small amount of water and stir to fully dissolve it; b. Pour the calculated amount of zinc oxide into the sodium hydroxide solution obtained in step a and stir to fully dissolve it; c. Pour the calculated amount of nickel sulfate into a small amount of water and stir to fully dissolve it; d. Pour the calculated amount of triethanolamine into the nickel sulfate solution obtained in step c and stir to fully dissolve it; e. Pour the calculated amount of tetraethylene pentamine, EDTA, and tartaric acid into a small amount of water, stir to fully dissolve, and pour into the solution obtained in d to fully dissolve; f. Mix the solution of step b and step e, stirring and dissolving until clear; J. Add the calculated amount of nano silicon oxide and nano titanium oxide to f, and stir evenly to make the nanoparticles suspended in the plating solution; h. Add the calculated amount of water to make up to volume.

[0009] The specific implementation steps of this embodiment are as follows: Embodiment 1:

[0010] a. Use sandpaper to smooth the sample; b. Rinse the sample with deionized water; c. Add 5.5% nickel sulfate and 4.5% triethanolamine to beaker A, and add 200mL deionized water to dissolve; d. Add 1.4% tetraethylene pentamine, 2.1% potassium sodium tartrate, and 0.2% EDTA to beaker B, add 100 mL of deionized water to dissolve, and then mix with the solution in beaker A; e. Add 77.7% sodium hydroxide to beaker C, add 200 mL of deionized water to dissolve, and stir until the solution is clear; f. Dissolve 2.8% zinc oxide in 100 mL of deionized water, stir until the solution is clear, slowly add to beaker C, and continue stirring until the solution is clear; g. Slowly add the solution in beaker C to beaker A under stirring, and then add 12mL primary brightener and 12mL secondary brightener; h. Finally, add 3.8% nano-silicon dioxide and 1.6% nano-titanium dioxide into beaker A. i. The mixed solution was fixed to 1000 mL and stirred to mix evenly; j. Take Q235 steel plate as cathode plate, and perform pretreatment according to the steps of substrate degreasing → water washing → pickling and rust removal → water washing → pickling and rust removal → water washing → activation; k. The plating time is 15 minutes, turn on the power, and use 4A / dm² for plating. Comparative Example 1:

[0011] a. Use sandpaper to smooth the sample; b. Rinse the sample with deionized water; c. Add 5.5% nickel sulfate and 4.5% triethanolamine to beaker A, and add 200mL deionized water to dissolve; d. Add 1.4% tetraethylene pentamine, 2.1% potassium sodium tartrate, and 0.2% EDTA to beaker B, add 100 mL of deionized water to dissolve, and then mix with the solution in beaker A; e. Add 77.7% sodium hydroxide to beaker C, add 200 mL of deionized water to dissolve, and stir until the solution is clear; f. Dissolve 2.8% zinc oxide in 100 mL of deionized water, stir until the solution is clear, slowly add to beaker C, and continue stirring until the solution is clear; g. Slowly add the solution in beaker C to beaker A under stirring, and then add 12mL primary brightener and 12mL secondary brightener; h. Finally, add 5.4% nano-silicon dioxide into beaker A. i. The mixed solution was fixed to 1000 mL and stirred to mix evenly; j. Take Q235 steel plate as cathode plate, and perform pretreatment according to the steps of substrate degreasing → water washing → pickling and rust removal → water washing → pickling and rust removal → water washing → activation; k. The plating time is 15 minutes, turn on the power, and use 4A / dm² for plating. Comparative Example 2:

[0012] a. Use sandpaper to smooth the sample; b. Rinse the sample with deionized water; c. Add 5.5% nickel sulfate and 4.5% triethanolamine to beaker A, and add 200mL deionized water to dissolve; d. Add 3.7% tetraethylene pentamine to beaker B, add 100mL of deionized water to dissolve it and mix it with the solution in beaker A; e. Add 77.7% sodium hydroxide to beaker C, add 200 mL of deionized water to dissolve, and stir until the solution is clear; f. Dissolve 2.8% zinc oxide in 100 mL of deionized water, stir until the solution is clear, slowly add to beaker C, and continue stirring until the solution is clear; g. Slowly add the solution in beaker C to beaker A under stirring, and then add 12mL primary brightener and 12mL secondary brightener; h. Finally, add 3.8% nano-silicon dioxide and 1.6% nano-titanium dioxide into beaker A. i. The mixed solution was fixed to 1000 mL and stirred to mix evenly; j. Take Q235 steel plate as cathode plate, and perform pretreatment according to the steps of substrate degreasing → water washing → pickling and rust removal → water washing → pickling and rust removal → water washing → activation; k. The plating time is 15 minutes, turn on the power, and use 4A / dm² for plating.

[0013] Compared with Example 1, Example 1 uses a dual nanometer system of nano-silicon oxide and nano-titanium oxide, while Example 1 only adds nano-silicon oxide and uses a single nanometer system. Compared with Example 2, Example 1 adds triethanolamine, tetraethylenepentamine, EDTA, potassium sodium tartrate and uses a multi-component complexing agent system, while Example 2 adds triethanolamine and tetraethylenepentamine and uses a binary complexing agent system. The comparison is mainly carried out through four items, including SEM (1 micron), nickel content, neutral salt spray test and Hull cell test for uniform plating Results comparison: Comparison items / samples Example 1 Comparative Example 1 Comparative Example 2 Nickel content 14.1% 13.4% 17.5% Neutral salt spray test 670 hours 408 hours 144 hours Throwing property 17cm 15cm 11cm Referring to the attached drawings, the SEM results show that the coating of Example 1 is smooth, the grains are dense, and there are no pinholes. There are a small number of pinholes in Comparative Example 1, and the grains are relatively coarse. Comparative Example 2 has more pinholes, coarse grains, and poor coating flatness. According to experience, the closer the nickel content of the coating is to 14%, the better its corrosion resistance, hardness and coating toughness. The results show that the nickel content of the coating of Example 1 is closest to 14%, so it has better corrosion resistance, hardness and toughness. The neutral salt spray test is an effective method to test the corrosion resistance of the coating. The longer the salt spray experiment is carried out, the better the corrosion resistance of the coating, and the bare plated coating on the market (the coating without any surface treatment measures after electroplating). According to GB / T 6458-86 "Neutral Salt Spray Test for Metal Coatings (NSS Test)", a salt spray test was conducted, and the test was stopped after red rust appeared on the coating and spread. The neutral salt spray test time of Example 1 reached 670 hours, far exceeding Comparative Examples 1 and 2. In the Hull cell test for uniformity, on a 20 cm plated sheet, the wider the coating coverage, the stronger the uniformity of the plating solution, and the stronger the uniformity, the better the electroplating ability for complex parts. In this test, the coating coverage of Example 1 reached 17 cm, also far exceeding Comparative Examples 1 and 2.

[0014] Therefore, the coating of the present invention has good compactness, low porosity, excellent corrosion resistance and good throwing power, and is suitable for complex parts such as high-speed train connectors.

Claims

1. A composite coating electroplating process, characterized in that: The plating solution comprises, by mole mass ratio, 50%-80% sodium hydroxide, 2%-3% ZnO, 3%-7% nickel sulfate, 2%-9% triethanolamine, 0.4%-3% tetraethylenepentamine, 1%-4% potassium sodium tartrate, 0.1%-1% EDTA, 2%-7% nano silicon dioxide, 0.6%-3% nano titanium oxide, 12mL / L primary brightener, 12mL / L secondary brightener; the process is as follows: temperature 15-30°C, plating solution pH: 12, cathode current density 4-6A / dm², cathode area: anode area is 1:1.2, and electroplating time: 15 minutes; the electroplating process comprises: a. Pour the calculated amount of sodium hydroxide into a small amount of water and stir to fully dissolve it; b. Pour the calculated amount of zinc oxide into the sodium hydroxide solution obtained in step a and stir to fully dissolve it; c. Pour the calculated amount of nickel sulfate into a small amount of water and stir to fully dissolve it; d. Pour the calculated amount of triethanolamine into the nickel sulfate solution obtained in step c and stir to fully dissolve it; e. Pour the calculated amount of tetraethylene pentamine, EDTA, and tartaric acid into a small amount of water, stir to fully dissolve, and pour into the solution obtained in d to fully dissolve; f. Mix the solution of step b and step e, stirring and dissolving until clear; J. Add the calculated amount of nano silicon oxide and nano titanium oxide to f, and stir evenly to make the nanoparticles suspended in the plating solution; h. Add the calculated amount of water to make up to volume.